Tribocorrosão da martensita de nitrogênio obtida por SHTPN sobre o aço AISI 409 - Souza, Amanda Pires Nogueira de (2020)
Several surface treatments have been applied to stainless steels with purpose to increase mechanical properties without damaging corrosion resistance. Among these, the Solution Heat Treatment after Plasma Nitriding (SHTPN) was able to provide an increase in both properties through the formation of nitrogen martensite. In this context, the purpose was to evaluate the tribocorrosion performance of SHTPN treated AISI 409 steel, quenching and tempering. After treatments, the samples were characterized by: x-ray diffraction (XRD), optical microscopy (MO), scanning electron microscopy (SEM), Vickers microhardness and nanoindentation. The corrosion resistance evaluated using the Tafel extrapolation technique in a solution of 0.5 Mol.L-1 NaCl. Electrochemical and friction coefficient measurements were used during bidirectional sliding to monitor the tribocorrosion behavior, using reciprocating tribometer integrated with a potentiostat. The corrosion quantification before and during sliding was analyzed by linear polarization resistance (RPL). Results indicated that the treatment of SHTPN promoted the formation of the martensitic nitrogen layer on the ferritic substrate. All treated samples showed hardness values higher than the untreated sample. The corrosion analyzes showed greater resistance for the condition SHTPN + TR250 (0.083 V vs. SHE) and less resistance for the condition SHTPN+TR650 (-187 V vs. SHE). For the results of tribocorrosion: The potential measurements of open circuit (OCP) were efficient in providing information about electrochemical state under tribological influence, showing the effect of the galvanic coupling during the test. The treated conditions exhibited greater resistance, that was independent of latency times. The condition SHTPN + TR450 exhibited greater tribocorrosion resistance compared to the other conditions, with less total wear volume under sliding; and lower resistance for the condition SHTPN+TR650.